2015
DOI: 10.1186/s12871-016-0212-3
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of APACHE II score and plasma suPAR in Chinese patients with sepsis: a prospective observational study

Abstract: BackgroundTimely risk stratification is the key strategy to improve prognosis of patients with sepsis. Previous study has proposed to develop a powerful risk assessment rule by the combination of Acute Physiology and Chronic Health Evaluation II (APACHE II) score and plasma soluble urokinase plasminogen activator receptor (suPAR). That reaffirmation of suPAR as a prognostic marker in Chinese patients with severe sepsis is the aim of the study.MethodsA total of 137 consecutive Chinese patients with sepsis were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 26 publications
2
19
1
3
Order By: Relevance
“…The median scorings in APACHE II and SAPS II were 25 and 56 points in the study group, which were much higher than in the above cited papers. Multi-organ failure may significantly interfere with the observations regarding the relationship between NLR and mortality [ 20 , 21 ]. However, this drawback could be interpreted as the strength of our research.…”
Section: Discussionmentioning
confidence: 99%
“…The median scorings in APACHE II and SAPS II were 25 and 56 points in the study group, which were much higher than in the above cited papers. Multi-organ failure may significantly interfere with the observations regarding the relationship between NLR and mortality [ 20 , 21 ]. However, this drawback could be interpreted as the strength of our research.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, APACHE II score at discharge was found to be able to predict the readmission to neurosurgery ICU, when the score is > 8.5, the patients may be suggested to extend ICU stay to reduce the readmission risk [15]. Compared with GCS score, APACHE II score was found to have better sensitivity and specificity in predicting the mortality of patients with brain traumatic injury [16] and if APACHE II score is ≥ 15, it predicts poor prognosis and low mortality [20].…”
Section: Discussionmentioning
confidence: 96%
“…In our study, we found that the SOFA score and APACHE II score within 24 hours after entering ICU were statistically signi cant in the univariate analysis, while the multivariate analysis showed that only APACHE II score 20 was an independent risk factor in this group. However, there was evidence that APACHE II score might provide inaccurate information in some patients, for example, in patients with unconsciousness, the score might be too high [26] . Therefore, we need to increase the sample size to con rm this result in the future.…”
Section: Discussionmentioning
confidence: 99%